A narrative review of running wearable measurement system accuracy and reliability: can we make running shoe prescription objective?. (4th May 2021) - Blazey, Paul; Michie, Tom V.; Napier, Christopher
Abstract: Running shoe prescription is based upon outdated paradigms, foremost the idea that correcting or preventing overpronation is desirable when attempting to prevent injury. Poor shoe prescription has the potential to affect an individual's performance and may lead to injury and withdrawal from a potentially lifelong healthful pursuit. In this systematic narrative review, we consider the evidence (validity and reliability) for implementing two types of wearable device: instrumented ' pressure sensing ' insoles and inertial measurement units (IMUs) to assess biomechanical data. The review summarizes existing data on the selection and placement, ability to capture kinetic and kinematic data effectively, and the limitations of both IMUs and pressure sensitive insoles for in-field measurement. We found that wearable devices have demonstrated an excellent level of reliability with some also showing good to excellent levels of validity to measure markers of potential interest in a future shoe prescription context. Further work is required to confirm which kinematic and/or kinetic measurements offer the greatest insight to individuals selecting their favoured shoe. Finally, we propose an objective alternative to the current shoe prescription rhetoric, based upon objective data collection using a wearable device.